Cars - Green, Rod; Hilborne, Jennifer; Pastor, terry (Dorking, England Templar Pub, 2011)
Wonderful bold colourful illustrations make these action-packed books are a little boy's dream. Turn the pages to reveal a pop-up vehicle that springs to life before your eyes. Five of the world's fastest, coolest, wildest cars are featured from a rally to a racing car, a vintage car and a safari jeep all brought to life with zappy text
Scientific notions
1
Keywords: Automobiles -- Juvenile literature; Automobiles; Pop-up books -- Specimens